Struktur Komunitas Makrofita Akuatik di Sungai Embau Kecamatan Hulu Gurung Kabupaten Kapuas Hulu - Tri Rima Setyawati, Irvan Fitra Jayadi, Riza Linda (Universitas Tanjungpura, 2017)
Aquatic macrophyte is one of macro plants that grows in or in near that water. The study aimed to know structure of aquatic macrophyte community plants in Embau river district of Hulu Gurung, Kapuas Hulu Regency. The research sample were taken in april 2016 using cover area transect. There are 15 species from 12 families of aquatic macrophytes found in the research site. Thirteen types of these plants are emergent such as Calla sp., Cyperus pilosus L., Chiloscypus polyanthos L., Dichodontium sp., Donax canniformes, Eleocharis pervula R.Br, Fissidens toxifolius L. Vhal, Fluminea festutacea, Eleusine indica (L) Gaertn, Homalomena sp., Monosolenium terenum, Polygonum sp. dan Rosmarinus sp. The two types of submerged plants found in the sampling site are Glossostigma sp., and Elodea sp. Species of F. toxifolius L. Vhal is one of aquatic macrophytes that had the highest cover area transect (CAT) with 18,1% while Eleusine indica (L) Gaertn had the lowest CAT with 1,39%. According diversity index aquatic macrophyte in Embau river was moderate (H’= 1,18-1,8), Index of dominace was low (C= 0,21-0,44) and high level of evenest index (E= 0,44-0,69). The Embau river is the highest polluted heavy metal of Plumbum (Pb2+) in sediment with 13,4 mg/l.